A description of verbal interaction in social studies class for fast learners - Capungcol, Nestor R. 1945-
The purpose of the study is two-fold: 1) to describe and analyze the characteristics and patterns of the teacher-pupil verbal interaction in social studies of the accelerated class at the Jose Rizal Elementary School, Pasay City, with the use of the Verbal Interaction Category System (VICS) by Amidon and Hunter, and 2) to gain insights in the teaching of social studies to gifted children. The significance of this study lies in providing teachers an objective tool through which they can look into their respective instructional behavior and into the effects of such behavior on the cognitive, affective and performative expressions and achievement of the students.